Lift the Flap Book Media Affect Disaster Preparedness in Early Childhood - Ulfah, Karima Ulya; Rolina, Nelva; Alfina, Cut Sarna (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Children are still not aware of the dangers of disasters; knowledge of preparedness is still lacking. Another problem is that children don't know exactly what to do before, during, or after a disaster. This research aims to analyze the influence of using the lift the flap book media "Let's be prepared for disasters" on disaster preparedness in early childhood. This research uses a quantitative approach with a quasi-experimental type with a nonequivalent control group design. The subjects in this study were divided into two classes, namely the experimental class and the control class with the total number of subjects being 80 Kindergarten B children. In the experimental class there were 40 children who used lift the flap book media, and in the control class there were 40 children who used conventional learning. The instrument used is a disaster preparedness instrument in the form of an observation sheet. The analysis technique uses the Independent Sample t-Test with a significance level of 0.05. The results of the research show that there is a difference. The results of the independent t test on the disaster preparedness variable obtained a t value of 32.822 and p = 0.000 < 0.05, so Ho is rejected, so it can be concluded that the hypothesis states that there is a significant influence of the use of lift the flap book media on the introduction of preparedness disasters in children aged 5-6 years.